Therapeutic Evaluation of Lodhradi Kashaya Ghanvati in Type II Diabetes Mellitus - Reddy, K. R. C. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: To evaluate the therapeutic effects of Lodhradi Kashaya Ghanvati (LKGV) in Type II diabetes mellitus (DM) patients. Materials and Methods: Forty-five patients of Type II DM were registered from the Outpatient Department of Rasa Shastra, Sir Sunderlal Hospital, Banaras Hindu University, Varanasi. Patients were randomly divided into three groups for the treatment of three different medicine groups (Group A - trial drug only [LKGV 500 mg TID] before meal; Group B - trial drug [LKGV 500 mg TID] before meal + glimepiride [1 mg OD] after meal; Group C - glimepiride treated [1 mg OD]). The treatment was given for 3 months. Fasting blood sugar, postprandial sugar, serum creatinine, blood urea, lipid profile, and serum glutamic oxaloacetic transaminase and serum glutamic pyruvic transaminase levels were estimated biochemically. Results: The results of the present study reveal that LKGV can be safe and effective, alternative or adjuvant to the conventional oral hypoglycemic agent. Conclusion: The ayurvedic herbal formulation along with the modern drug is the need of hour to take more benefits for the human society suffering from lifestyle disorders.